The Role Of Tumor Markers In The Diagnosis And Follow Up In Patients With Pancreatic Cancer - Al-Bayatti, Ansam Aladdin (Journal of the Faculty of Medicine Baghdad, 2007)
Background: To shade a light on certain tumor markers and their sensitivity and specificity in determination of pancreatic cancer. Patients & Methods :- A total of 35 patients with pancreatic cancer were studied between June 2003 and April 2004 in Specialized Surgical - Baghdad Teaching Hospital . These patients were compared with other 25 non malignant G.I diseases patients as well as 35 healthy controls . The serum was estimated for CAI 9-9 , and CEA by ELFA (Enzyme Linked Fluorescent Assay) method and CPR by ELISA method. Results :- Five patients with pancreatic cancer were excluded from this study because they were beyond surgery.The results show that there is significant differences between serum level of CAI 9- 9 in pancreatic cancer patients as compared with the non malignant G.I disease patients group and control (P< 0.05). While for the determination of CEA there is also significant difference between the pancreatic patients group as compared with the non malignant G.I patients group and control group (P< 0.05). As for the result of CRP there is also significant difference between the pancreatic patients group and the non malignant G.I patients group and control group (P< 0.05) . Conclusion :- Significant differences were found in the result of the tumor markers CA 19-9 , CEA , and CRP studied in patients with pancreatic cancer as compared with the other non malignant G.I patients and controls . The sensitivity for using all the mentioned parameters was 90% were as the specificity was 75%.